Injection of multiple shattered pellets for disruption mitigation in DIII-D. (4th September 2019) - Herfindal, J.L.; Shiraki, D.; Baylor, L.R.; Eidietis, N.W.; Hollmann, E.M.; Lasnier, C.J.; Moyer, R.A.
Abstract: Plasma shutdown experiments in DIII-D have injected multiple shattered pellets at different toroidal locations for the first time, as is planned for the ITER disruption mitigation system. Systematically varying the relative timing of the two pellets suggests that simultaneously injected pellets may influence the assimilation of each other, altering the resulting disruption characteristics compared to a single pellet injecting similar neon quantities. Thermal quench (TQ) radiation measured near the injection location is reduced with the dual pellets, contrary to TQ radiation measured away from the injection ports, which does not show a clear difference between single or dual pellet injections. The mitigation of other disruption loads, such as the current quench (CQ) duration and divertor heat loads, decrease when the pellets enter the plasma simultaneously compared to single shattered pellet injections with similar neon quantities. This similar reduction in mitigation of CQ and conductive loads is consistent with the observed reduction in total TQ radiation. The time between initial pellet injection and the end of the TQ is shorter when both pellets are injected simultaneously compared to a single pellet. This lower cooling duration may limit the amount of the neon assimilated by the plasma prior to the end of the TQ, consistent with the observed reduction in radiation. The injected impurities spread primarily in the parallel direction, away from the source at the injection location. The addition of two shattered pellet injectors shows that the initial poloidal radiation is spread out into two distinct regions, cooling multiple flux tubes simultaneously, which may induce global MHD instabilities more rapidly than a single flux tube of impurities leading to a shorter cooling duration. The electron density increased by approximately a factor of two with the addition of multiple pellets, but is highly sensitive to the time between injections. A maximum density increase is found when both pellets arrive at the plasma prior to the start of the TQ.